2019
DOI: 10.1158/1078-0432.ccr-18-3344
|View full text |Cite
|
Sign up to set email alerts
|

CAF-Derived IL6 and GM-CSF Cooperate to Induce M2-like TAMs–Response

Abstract: We read with great interest the letter by Iorio and colleagues entitled "Cancer-stimulated CAFs enhance monocyte differentiation and pro-tumoral TAM activation" in this issue of Clinical Cancer Research, which provides valuable context and additional discussion of our recent article in this journal. In their letter, the authors reevaluated their recent work on the role of BAG3, a regulator of chaperone-assisted selective autophagy, which inhibits tumorigenesis and metastasis in pancreatic ductal adenocarcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In our model, macroH2A-dependent regulatory mechanisms converged on a small set of inflammatory genes, which underscores a role for macroH2A in limiting inflammatory signalling in vivo. Notably, CAFs hijack these inflammatory genes as a mechanism of tumour immune escape 80 83 , and our studies suggest that dKO CAFs promote an immunosuppressive environment that leads to increased melanoma burden (Fig. 7h ).…”
Section: Discussionmentioning
confidence: 58%
“…In our model, macroH2A-dependent regulatory mechanisms converged on a small set of inflammatory genes, which underscores a role for macroH2A in limiting inflammatory signalling in vivo. Notably, CAFs hijack these inflammatory genes as a mechanism of tumour immune escape 80 83 , and our studies suggest that dKO CAFs promote an immunosuppressive environment that leads to increased melanoma burden (Fig. 7h ).…”
Section: Discussionmentioning
confidence: 58%
“…Recombinant human granulocyte colony-stimulating factor (rhGCSF) has been widely used in the treatment of granulocytopenia induced by chemoradiotherapy. In vitro studies have shown that CSF can also be produced by tumor cells and stromal cells, and it could promote tumor fitness and cell proliferation and metastasis 67 . Patients with high CSF expression have a rapid disease progression and short survival time.…”
Section: Expression and Significance Of Csf-1 And Csf-1r In Gastrointestinal Malignant Tumorsmentioning
confidence: 99%